Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.5194/tc-8-891-2014
|View full text |Cite
|
Sign up to set email alerts
|

The microwave emissivity variability of snow covered first-year sea ice from late winter to early summer: a model study

Abstract: Abstract. Satellite observations of microwave brightness temperatures between 19 GHz and 85 GHz are the main data sources for operational sea-ice monitoring and retrieval of ice concentrations. However, microwave brightness temperatures depend on the emissivity of snow and ice, which is subject to pronounced seasonal variations and shows significant hemispheric contrasts. These mainly arise from differences in the rate and strength of snow metamorphism and melt. We here use the thermodynamic snow model SNTHERM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 49 publications
3
43
1
1
Order By: Relevance
“…The variation amounts to approximately 20-30 K, which corresponds to about 8-12 % of the average value, and the peaks in the variation occur in summer. Thus, increased variability in late spring/early summer connected to melt onset and consequent snow metamorphoses, reported by Willmes et al (2014), is confirmed in our study.…”
Section: Dynamic Tie Pointssupporting
confidence: 78%
See 2 more Smart Citations
“…The variation amounts to approximately 20-30 K, which corresponds to about 8-12 % of the average value, and the peaks in the variation occur in summer. Thus, increased variability in late spring/early summer connected to melt onset and consequent snow metamorphoses, reported by Willmes et al (2014), is confirmed in our study.…”
Section: Dynamic Tie Pointssupporting
confidence: 78%
“…Effect of diurnal, regional and inter-annual variability of atmospheric forcing on surface microwave emissivity was also reported in a model study of Willmes et al (2014). This means that not only sea ice area has a climatic trend, but atmospheric and surface parameters affecting the microwave emission may also have a trend.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, ice-snow interface flooding, formation of meteoric ice and snow metamorphism all impact sea ice concentrations, which have not been quantified yet for Antarctic sea ice, and trends in brightness temperatures found in the Weddell Sea may reflect increased melt rates or changes in the melt season (Willmes et al, 2014). The advantage of the Bootstrap algorithm is that the ice concentration can be derived without an a priori assumption about ice type, though consolidated ice data points are sometimes difficult to distinguish from mixtures of ice and open ocean due to the presence of snow cover, flooding or roughness effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, another complication is that seasonal variations in sea ice and snow emissivity can be very large, leading to seasonal biases in either algorithm (e.g., Andersen et al, 2007;Willmes et al, 2014;Gloersen and Cavalieri, 1986). In addition, ice-snow interface flooding, formation of meteoric ice and snow metamorphism all impact sea ice concentrations, which have not been quantified yet for Antarctic sea ice, and trends in brightness temperatures found in the Weddell Sea may reflect increased melt rates or changes in the melt season (Willmes et al, 2014).…”
Section: Discussionmentioning
confidence: 99%